(untitled) (Journal of Global Humanities and Social Sciences, 2025)
In recent years, people are more and more concerned about the safety of drinking water, with the improvement of the quality of life, urban drinking water is facing multiple pressures of demand and environmental protection, how to ensure the safety of urban drinking water quality under the development of the new era is an important task of urban development. This paper firstly elaborates on the safety of urban drinking water, then analyzes in detail some practical problems faced by urban drinking water quality safety, and finally puts forward some specific measures to ensure the safety of urban drinking water quality.